New members of the family Eggerthellaceae isolated from Marmota himalayana: Xiamenia xianingshaonis gen. nov., sp. nov., from intestinal contents, and Berryella wangjianweii sp. nov., from trachea. Issue 9 (15th September 2022) - Zhang, Gui; Lv, Xianglian; Cheng, Yanpeng; Lai, Xin-He; Yang, Jing; Jin, Dong; Lu, Shan; Pu, Ji; Liu, Liyun; Xu, Jianguo
Abstract : Four strictly anaerobic, Gram-stain-positive, urease-, oxidase- and catalase-negative, rod-shaped strains (zg-886 T /zg-887 and zg-1050 T /zg-1084) were isolated from Marmota himalayana . Comparison analysis of 16S rRNA genes showed that the two strain pairs belong to the family Eggerthellaceae : zg-1050 T and zg-1084 were most closely related to Berryella intestinalis 68-1-3 T (97.2 %), while zg-886 T /zg-887 had the highest similarity to Slackia piriformis YIT 12062 T (91.6 %), followed by Paraeggerthella hongkongensis DSM 16106 T (91.4 %) and Gordonibacter urolithinfaciens DSM 27213 T (91.4 %). Phylogenetic analyses based on 16S rRNA genes and genomes showed that the two strain pairs represent two different lineages within the family Eggerthellaceae . The genomic G+C contents of strains zg-886 T and zg-1050 T were 63.0 and 66.3 mol%, respectively. The values of digital DNA–DNA hybridization, average nucleotide identity, average amino acid identity and the percentage of conserved proteins between the two new type strains and members of the family Eggerthellaceae were lower than the respective thresholds for delineation of a species or genus. In contrast to the absence of any known quinones in strain zg-1050 T, strain zg-886 T contained MK-6 (42.5 %), MMK-6 (25.0 %) and DMMK-6 (32.5 %). The four strains grew optimally at pH 7.0, 37 ºC and 0.5 % NaCl (w/v). According to these polyphasic analyses, two new members within the family Eggerthellaceae are proposed, Xiamenia xianingshaonis gen. nov., sp. nov. (zg-886 T =JCM 34097 T =GDMCC 1.1710 T ) and Berryella wangjianweii sp. nov. (zg-1050 T =GDMCC 1.2426 T =JCM 34748 T ).